From Paul to Valentinus : Christians at Rome in the first two centuries - Lampe, Peter, 1954-; Johnson, Marshall D. (Minneapolis : Fortress Press, 2003)
"Investigating the rise and shape of the earliest churches in Rome, Lampe integrates history, archaeology, theology, and social analysis. He also takes a close look at inscriptional evidence to complement the reading of the great literary texts: from Paul's letter to the Romans to the writings of Clement of Rome, Justin Martyr, Montanus, and Valentinus. This study is a groundbreaking work - broad in scope and closely detailed. Lampe deals with the shape of leadership and the followers of Christ in relation to the Judeans living in Rome."--BOOK JACKET.
Foreword / Robert Jewett -- Pt. 1. Introduction: From the Beginnings of Urban Roman Christianity to the Separation from the Synagogue -- Ch. 1. The Entrance of Christianity via the Trade Route -- Ch. 2. The "Edict of Claudius" and Separation from the Synagogue -- Pt. 2. Topography -- Ch. 3. In Which Quarters of the City Did the Christian Population Concentrate? -- Ch. 4. Did Particular Strata of the Population Predominate in the Quarters under Investigation? -- Pt. 3. First Diachronic Section: General Information About Urban Roman Christianity -- Ch. 5. Jewish and Gentile Christians -- Ch. 6. Information from Paul's Letter to the Romans and Acts 28:30f. -- Ch. 7. Information in Conjunction with the Persecution by Nero -- Ch. 8. Information from First Clement -- Ch. 9. Information from Ignatius's Letter to the Romans -- Ch. 10. The Shepherd of Hermas: Social Stratification in the First Half of the Second Century and the Attendant Conflicts -- Ch. 11. The Writings of Justin: The Social Structure of Christianity at the Middle of the Second Century -- Ch. 12. The Excavation Complex at the Vatican -- Ch. 13. Social Stratification at the Time of Commodus -- Ch. 14. Traditio Apostolica -- Ch. 15. Summary and Conclusion -- Pt. 4. Second Diachronic Section: Prosopographic Investigation -- Ch. 16. The Roman Christians of Romans 16 -- Ch. 17. Claudius Ephebus and Valerius Biton (I Clem. 63:3; 65:1) -- Ch. 18. Aquila and Prisca -- Ch. 19. Pomponia Graecina -- Ch. 20. T. Flavius Clemens and Flavia Domitilla -- Ch. 21. The Author of First Clement -- Ch. 22. The Person of Hermas -- Ch. 23. The Woman from Justin's Apology 2.2 -- Ch. 24. Marcion -- Ch. 25. Justin -- Ch. 26. Tatian and Rhodon -- Ch. 27. Valentinians -- Ch. 28. Carpocratians -- Ch. 29. The Martyr Apollonius -- Ch. 30. Marcus Aurelius Prosenes and Other Members of Caeser's Familia -- Ch. 31. Two Wives of Governors: Women of Senatorial Rank -- Ch. 32. Representatives of Western Latin Education -- Ch. 33. The Theodotians -- Ch. 34. Praxeas, Gaius, and the Problem of "Hippolytus" -- Ch. 35. Summary -- Pt. 5. The Fractionation of Roman Christianity -- Ch. 36. The Evidence of Fractionation -- Ch. 37. Private Property Utilized by the Church Community -- Ch. 38. The Exeternal Image of Christian House-Church Congregations -- Ch. 39. Fractionation and Theological Pluralism -- Ch. 40. Fractionation and Tolerance of People with Other Theological Opinions -- Ch. 41. Fractionation, Monarchical Episcopacy, and Presbyterial Governance -- Pt. 6. Final Remarks -- App. 1. Students of Marcion -- App. 2. Justin: Educational Components -- App. 3. Tatian: Education Components -- App. 4. Fractionation of Roman Jewry.
Translated from the 2nd German ed. (1989)
Includes bibliographical references (p. 437-474) and indexes.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Rome (Italy) -- Church history; Rome (Italy) -- Social life and customs